1998
DOI: 10.3354/dao032161
|View full text |Cite
|
Sign up to set email alerts
|

Replication of a herpes-like virus in larvae of the flat oyster Tiostrea chilensis at ambient temperatures

Abstract: Veligers removed from brooding T~ostrea chilens~s (Philippi, 1845) experienced -95% mortalities over 3 to 4 d at 16 to 18°C that appeared to be associated with a herpes-like virus. Ultrastructural observations of post-removal veligers showed the presence of early viral replication or putative latent stages at 4 h, all stages of replication at low levels at 24 h, which increased to high levels at 48 h, followed by mortalities at 72 h onwards. Initially, infected interstitial or epithelia1 cells had an enlarged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 21 publications
1
57
0
1
Order By: Relevance
“…Several herpes-like virus infections have been reported in marine vertebrates and invertebrates, including ostreid bivalves (Farley et al 1972, Hine et al 1992, Nicolas et al 1992, Comps & Cochennec 1993, Renault et al 1994a, Hine & Thorne 1997, Hine et al 1998. We describe for the first time a herpes-like virus in Manila clam larvae associated with high mortality rates in France.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Several herpes-like virus infections have been reported in marine vertebrates and invertebrates, including ostreid bivalves (Farley et al 1972, Hine et al 1992, Nicolas et al 1992, Comps & Cochennec 1993, Renault et al 1994a, Hine & Thorne 1997, Hine et al 1998. We describe for the first time a herpes-like virus in Manila clam larvae associated with high mortality rates in France.…”
Section: Discussionmentioning
confidence: 93%
“…Hine et al (1992) described a herpes-like virus infection responsible for mortality of hatchery-reared C. gigas larvae in New Zealand. Herpes-like viruses were also observed in haemocytes of Ostrea angasi adults in Australia (Hine & Thorne 1997) and in larval New Zealand flat oysters Tiostrea chilensis (Hine et al 1998). All these viruses are similar with respect to morphology and cellular localisations and so far have only been detected in Ostreidae (Renault 1998).…”
Section: Introductionmentioning
confidence: 90%
“…Studies conducted during the 1990s demonstated the presence of herpesvirus-like particles in Ostrea angasi (flat oyster) (Hine & Thorne 1997) in Australia and in Crassostrea gigas (Hine et al 1992) and Ostrea chiliensis (Hine et al 1998) in New Zealand; however, molecular methods for the detection of OsHV-1 were not used and the identity of these herpesvirus-like particles was not established. In this study we have reported on the first confirmed outbreak of disease due to OsHV-1 infection in C. gigas in Australia.…”
Section: Discussionmentioning
confidence: 99%
“…Herpes-like virus particles have been observed in moribund Crassostrea gigas and Ostrea chilensis in New Zealand (Hine et al 1992(Hine et al , 1998, in Bonamia-infected O. angasi (Hine & Thorne 1997) and in hatcheryreared Saccostrea glomerata larvae experiencing mortalities (M. Hine pers. comm.)…”
Section: Introductionmentioning
confidence: 99%
“…Par la suite, des virus de type herpès ont été mis en évidence dans un large spectre de bivalves dont différentes espèces d'huîtres, de palourdes et la coquille Saint Jacques (Renault & Novoa, 2004). Ils ont ainsi été décrits aux USA (Farley et al 1972, Friedman et al 2005, Meyers et al 2009), en Nouvelle Zélande (Hine et al 1992 ;Hine et al 1998), en France (Nicolas et al 1992 ;Comps & Cochennec, 1993 ;Renault et al 1994aRenault et al , 1994bRenault et al 2000aRenault et al , 2000bArzul et al 2001aArzul et al , 2001bArzul et al , 2001cRenault et al 2001aRenault et al , 2001b, en Australie (Hine & Thorne, 1997) (Hooper et al 2007 ;Tan et al 2008) associés à des épi-sodes de mortalité massive à Taiwan et en Australie. Un variant du virus, dénommé OsHV-1var, a été rapporté chez différentes espèces de bivalves incluant l'huître creuse C. gigas (Arzul et al 2001a ;2001b, 2001c.…”
Section: Virus De Type Herpès Et Herpèsvirus Infectant Les Mollusquesunclassified